Experimental determination of CePO4 and YPO4 solubilities in H2O–NaF at 800°C and 1 GPa: implications for rare earth element transport in high‐grade metamorphic fluids. Issue 3 (13th April 2013) - Tropper, P.; Manning, C. E.; Harlov, D. E.
Abstract: Monazite (CePO4 ) and xenotime (YPO4 ) are important accessory minerals in metasediments. They host significant rare earth elements (REE) and are useful for geochronology and geothermometry, so it is essential to understand their behavior during the metasomatic processes that attend high‐grade metamorphism. It has been proposed that F‐bearing fluids enhance solubility and mobility of REE and Y during high‐grade metamorphism. We assessed this possibility by determining the solubility of synthetic CePO4 and YPO4 crystals in H2 O–NaF fluids at 800°C and 1 GPa. Experiments used hydrothermal piston‐cylinder and weight‐loss methods. Compared to the low solubilities of CePO4 and YPO4 in pure H2 O (0.04 ± 0.04 and 0.25 ± 0.04 millimolal, respectively), our results indicate an enormous increase in the solubility of both phosphates with increasing NaF concentration in H2 O: CePO4 solubility reaches 0.97 molal in 20 mol.% NaF, and YPO4 shows an even stronger solubility enhancement to 0.45 molal in only 10 mol.% NaF. The greatest relative solubility increases occur at the lowest NaF concentration. The solubilities of CePO4 and YPO4 show similar quadratic dependence on NaF, consistent with possible dissolution reactions of: CePO4  + 2NaF =  CeF2 +  + Na2 PO4 − and YPO4  + 2NaF = YF2 +  + Na2 PO4 − . Solubilities of both REE phosphates are significantly greater in NaF than in NaCl at equivalent salt concentration. A fluid with 10 mol.% NaCl and multiply saturated with fluorite, CePO4, and YPO4 would contain 1.7 millimolal Ce and 3.3 millimolal Y, values that are respectively 2.1–2.4 times greater than in NaCl‐H2 O alone. The results indicate that Y, and by extension heavy rare earth elements (HREE), can be fractionated from LREE in fluorine‐bearing saline brines which may accompany granulite‐facies metamorphism. The new data support previous indications that REE/Y mobility at these conditions is enhanced by complexing with F in the aqueous phase. Abstract : The solubility of synthetic CePO4 and YPO4 crystals in H2 O–NaF fluids at 800°C and 1 GPa has been determined. Solubilities of both rare earth elements (REE) phosphates are significantly greater in NaF than in NaCl at equivalent salt concentration. The results indicate that Y, and by extension HREE, can be fractionated from LREE in fluorine‐bearing saline brines which may accompany granulite‐facies metamorphism. The new data support previous indications that REE/Y mobility at these conditions is enhanced by complexing with F in the aqueous phase.